Extraction of bioactive compounds from hibiscus and jasmine flowers using microwaveassisted hydrodistillation (MAHD) and hydrodistillation (HD) methods - Alaaddin Rassem, Hesham Hussein (2020)
The use of natural origin essential oil has recently gained much attention in many fields such as food flavoring, pesticides and in pharmaceutical industries. However, limitations to the use of existing conventional extraction methods are the inherent time consumption, high cost, high power consumption, potential loss of volatile compounds from essential oil as well as environmental concerns. Therefore new innovation extraction techniques are required to overcome these limitations. In this research, essential oil was extracted from Hibiscus flower and Jasmine flower by using conventional hydrodistillation (HD) and non-conventional microwave assisted hydrodistillation (MAHD) methods. The influence of pre-treatment on the Hibiscus flower and Jasmine flower prior to extraction was investigated. Also, changes in morphology of the Hibiscus flower powder and Jasmine flower powder before and after extraction by the two methods was observed through SEM. Milder disruption of Hibiscus flower oil gland were observed for MAHD compared to HD. This is associated with the effective heat distribution obtainable from MAHD. The efficiency of MAHD extraction technique was compared with HD in terms of chemical composition and biological activity of the oil obtained as well as cost implication of the extraction process. To justify the performance of MAHD technique, the three main influencing factors such as solvent–to-plant material ratio, extraction time and irradiation microwave power were analyzed. Analysis of these factors was initially carried out using one factor at a time method. Furthermore, screening and optimization of the factors was conducted with the help of Design expert software via factorial analysis and central composite design, respectively. The optimum conditions obtained through CCD for MAHD is 120 min extraction time, 8:1 of methanol to raw material ratio and 300 W irradiation microwave power. The maximum yield obtained from Hibiscus and Jasmine flowers is 1.25 % and 1.21 %, respectively. On the other hand, the extraction parameters for HD are 160 min extraction time, 8:1 of methanol to raw material ratio and a constant operating power 350 W. The maximum yield obtained from Hibiscus and Jasmine flowers for HD is 1.15 % and 1.13 %, respectively. The essential oil obtained at the optimum operating conditions for both methods was subjected to further qualitative analysis. Compositional analysis was conducted through gas chromatography-mass spectrometer. A total of 37 compounds were found in both extraction methods (MAHD and HD) for Hibiscus flower oil which were supported by fourier transforms infrared spectroscopy analysis. However, the active compound present in Hibiscus flower oil (Ethanimidic acid, ethyl ester) manifested a mean value of 31.48 ± 0.2 and 29.23 ± 0.2 for MAHD and HD, respectively. Similarly, the collection of 10 compounds was obtained both extraction methods for Jasmine flower oil which were supported by FTIR analysis. However, the active compound present in Jasmine flower oil (2- Phenylthiolane) manifested a mean value of 57.31 ± 0.1 and 57.21 ± 0.1 for MAHD and HD, respectively. In addition, the antioxidant properties exhibited by Hibiscus and Jasmine flowers crude obtained through MAHD was evaluated against DPPH Scavenging Radical Assay. Interestingly, the crude extract obtained through MAHD shows IC50 value of 0.7 ppm and 5.15 ppm for Hibiscus and Jasmine flowers, respectively. This indicates that the MAHD technique is suitable for obtaining volatile oils from Hibiscus flower and Jasmine flower and the oils obtained can offer great pharmaceutical benefits.